Comparison of anatomical-based vs. nTMS-based risk stratification model for predicting postoperative motor outcome and extent of resection in brain tumor surgery - Ivren, Meltem; Grittner, Ulrike; Khakhar, Rutvik; Belotti, Francesco; Schneider, Heike; Pöser, Paul; D'Agata, Federico; Spena, Giannantonio; Vajkoczy, Peter; Picht, Thomas; Rosenstock, Tizian (NeuroImage: Clinical, 2023)
Background - Two statistical models have been established to evaluate characteristics associated with postoperative motor outcome in patients with glioma associated to the motor cortex (M1) or the corticospinal tract (CST). One model is based on a clinicoradiological prognostic sum score (PrS) while the other one relies on navigated transcranial magnetic stimulation (nTMS) and diffusion-tensor-imaging (DTI) tractography. The objective was to compare the models regarding their prognostic value for postoperative motor outcome and extent of resection (EOR) with the aim of developing a combined, improved model. - Methods - We retrospectively analyzed a consecutive prospective cohort of patients who underwent resection for motor associated glioma between 2008 and 2020, and received a preoperative nTMS motor mapping with nTMS-based diffusion tensor imaging tractography. The primary outcomes were the EOR and the motor outcome (on the day of discharge and 3 months postoperatively according to the British Medical Research Council (BMRC) grading). For the nTMS model, the infiltration of M1, tumor-tract distance (TTD), resting motor threshold (RMT) and fractional anisotropy (FA) were assesed. For the PrS score (ranging from 1 to 8, lower scores indicating a higher risk), we assessed tumor margins, volume, presence of cysts, contrast agent enhancement, MRI index (grading white matter infiltration), preoperative seizures or sensorimotor deficits. - Results - Two hundred and three patients with a median age of 50 years (range: 20-81 years) were analyzed of whom 145 patients (71.4%) received a GTR. The rate of transient new motor deficits was 24.1% and of permanent new motor deficits 18.8%. The nTMS model demonstrated a good discrimination ability for the short-term motor outcome at day 7 of discharge (AUC = 0.79, 95 %CI: 0.72-0.86) and the long-term motor outcome after 3 months (AUC = 0.79, 95 %CI: 0.71-0.87). The PrS score was not capable to predict the postoperative motor outcome in this cohort but was moderately associated with the EOR (AUC = 0.64; CI 0.55-0.72). An improved, combined model was calculated to predict the EOR more accurately (AUC = 0.74, 95 %CI: 0.65-0.83). - Conclusion - The nTMS model was superior to the clinicoradiological PrS model for potentially predicting the motor outcome. A combined, improved model was calculated to estimate the EOR. Thus, patient counseling and surgical planning in patients with motor-associated tumors should be performed using functional nTMS data combined with tractography.